Species diversity of macrofungi on fallows in the buffer zones of the landscape parks in Łódzkie province - Adamczyk, Jolanta (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2014)
This study presents the species structure of macrofungi in different plant communities formed on fallows as a result of secondary succession. The mycological observations were carried out in 2012 and 2013 in the buffer zones of all landscape parks in the Łódzkie province, i.e. Bolimów LP, Spała LP, Sulejów LP, Warta-Widawka LP, Łódź Hills LP, Przedbórz LP and Załęcze LP. The botanical research identified fallows representing 7 types of plant communities. In total 46 macromycetes species were found on the fallows. The diversity of macrofungi depended on the type of plant community. The highest number of fungi species was found in the communities with an admixture of trees (Pinus sylvestris, Betula pendula), while the lowest was collected on fallows almost completely covered by Cirsium arvense and Solidago canadensis. Considering the trophic classification of macrofungi found on fallows, most species were saprotrophic and mycorrhizal. Wood inhabiting saprotrophs were represented by only two species.